Jus Cogens Sebagai Dasar Mengikatnya Hukum Internasional - B. Lora Christyanti (Fakultas Hukum Universitas Islam Malang, 2022)
In the international relations, the relation between states is not a single dimension relation. Thus, it needs a regulation that applied universally. International law, do not own legal binding, has no strong legal position. Thus, it is needed to conduct a research on how is the legal standing of international law as a legal binding? This kind of research is a normative legal research conducted by secondary data. Based on the research, international law acquired their legal bonding form the paradigm of the natural law, which recognizes the universal norms, which is also known by international law as jus cogens. To strengthen the position of universal norms, jus cogens is codified in the Vienna Convention on The Law of Treaties on 1969, hence approved by positivists as a peremptory norm.